The Development E-Ting Application To Improve The English Writing Skill - Yuyun Bahtiar; Nur Herlina; Iin Baroroh Ma’arif; Luluk Choirun Nisa’ Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In English there are four skills namely reading, writing, listening and speaking. Speaking can be done spontaneously very different from writing which must pay attention to grammar and others, the purpose of this study is to design an android application that can help students develop their writing skills. This study uses the research and development method with the ADDIE model to design an application called